2021
DOI: 10.1186/s40779-021-00307-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between medical resources and the proportion of oldest-old in the Chinese population

Abstract: The potential association between medical resources and the proportion of oldest-old (90 years of age and above) in the Chinese population was examined, and we found that the higher proportion of oldest-old was associated with the higher number of beds in hospitals and health centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In contrast with older adults, younger individuals are more resilient to general physical stresses and external trauma ( 24 ). However, aging leads to declining functional abilities among older adults ( 25 ), resulting in a greater need for medical resources and care services ( 26 ). Accordingly, families must provide more significant and better resources to older adults to sustain their well-being and quality of life, including preserving their hearing health, which places a substantial financial burden on households.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with older adults, younger individuals are more resilient to general physical stresses and external trauma ( 24 ). However, aging leads to declining functional abilities among older adults ( 25 ), resulting in a greater need for medical resources and care services ( 26 ). Accordingly, families must provide more significant and better resources to older adults to sustain their well-being and quality of life, including preserving their hearing health, which places a substantial financial burden on households.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies [ 2 4 , 21 , 22 ], the burden of genitourinary cancers was highest in elderly men. The aging population clearly affects the burden of disease, but cancer-related risk factors also play an important role [ 23 27 ]. Smoking, a risk factor shared by all three genitourinary showed a decreasing contribution to cancer death and DALYs in the past 30 years, suggesting the past/current tobacco control strategies are effective.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies based on the GBD 2017 data have also shown that the burden of genitourinary cancers in the elderly was more serious [2-4, 17, 18]. The aging population and the increase in life expectancy are one of the factors that affect the burden of disease, but cancer-related risk factors also play an important role [19][20][21][22][23]. Smoking is a shared risk factor for these three cancers and shows a decreasing contribution to cancer death and DALYs in the past 30 years.…”
Section: Discussionmentioning
confidence: 99%